Financial Performance, Macroeconomics, And Systematic Risk On Islamic Stocks Of Manufacturing Entities - Rizky Siswanto; Sigid Eko Pramono; Rifki Ismal (Jurnal Akuntansi dan Keuangan Islam, 2022)
This study is to examine and analyze the effect of financial performance as measured by Return On Assets (ROA), Current Ratio (CR) and Earning Per Share (EPS), macroeconomic indicators using the BI rate, exchange rate and inflation as well as adding systematic risk as an intervention variable to the Islamic stock returns in the manufacturing sector on the Indonesian Sharia Stock Index (ISSI). The research sample was 51 companies with observations from 2016 to 2020, using the Structural Equation Modeling (SEM) method and IBM AMOS (Analysis of Structural Moment) V.22 software to test the available data. The direct test results show that financial performance and systematic risk have an effect on Islamic stock returns, while macroeconomic indicators have no effect. The test results through the intervention variables show that financial performance has an effect, but macroeconomic indicators still have no effect on Islamic stock returns through systematic risk. The activities of the consumer goods industry and basic industry which have always been the main needs are the reason why issuers in the manufacturing sector at ISSI are not affected by changes in macroeconomic indicators.Penelitian ini untuk menguji dan menganalisis pengaruh kinerja keuangan yang diukur dengan Return On Assets (ROA), Current Ratio (CR) dan Earning Per Share (EPS), indikator makroekonomi menggunakan BI rate, nilai tukar dan inflasi serta menambahkan risiko sistematis sebagai variabel intervensi terhadap return saham syariah sektor manufaktur pada Indeks Saham Syariah Indonesia (ISSI). Sampel penelitian sebanyak 51 perusahaan dengan pengamatan dari tahun 2016 sampai dengan tahun 2020 menggunakan metode Structural Equation Modeling (SEM) dan software IBM AMOS (Analysis of Structural Moment) V.22 untuk menguji data yang tersedia. Hasil pengujian langsung menunjukkan bahwa kinerja keuangan dan risiko sistematik berpengaruh terhadap return saham syariah, sedangkan indikator makroekonomi tidak berpengaruh. Hasil pengujian melalui variabel intervensi menunjukkan bahwa kinerja keuangan berpengaruh, namun indikator makroekonomi masih belum berpengaruh terhadap return saham syariah melalui risiko sistematis. Aktivitas industri barang konsumsi dan industri dasar yang selalu menjadi kebutuhan utama menjadi alasan emiten di sektor manufaktur di ISSI tidak terpengaruh oleh perubahan indikator makroekonomi.